The effect of youths as change agents on cardiovascular disease risk factors among adult neighbours: a cluster randomised controlled trial in Sri Lanka - Nadeeka Chandraratne; Miwa Yamaguchi; Susantha Indrawansa; Nalika Gunawardena; Keisuke Kuwahara; Zobida Islam; Yohei Kawasaki; Tetsuya Mizoue; Diyanath Samarasinghe (BMC, 2019)
Abstract Background Mobilising non-professional health workers has been successful in improving community health, but the effectiveness of an education program targeting youths in a community-based approach remains unclear. The objective of this study was to investigate the effect of an intervention with youth on cardiovascular disease risk factors of community adults. Methods A 12-month cluster randomised trial was conducted in a semi-urban area of Colombo in Sri Lanka. Facilitators trained youth club members aged 15-29 years to assess cardiovascular disease risk factors and take actions in the community to address relevant issues. The control group received no intervention. Body weight and blood pressure as primary outcomes and lifestyle of adults as secondary outcomes were measured pre- and post-intervention. Multilevel linear and logistic regressions were used to assess the effects of the intervention on changes in continuous and binary outcomes, respectively, from baseline to endpoint. Results Of 512 participants at baseline, 483 completed the final assessment after the intervention. Regarding primary outcomes, the intervention group showed a significantly greater decrease in body weight after intervention than the control group. The mean (95% confidence interval) difference of body weight change for intervention versus control group was − 2.83 kg (− 3.31, − 2.35). There was no statistically significant difference in blood pressure between the two groups. Turning to the secondary outcomes, in diet, the intervention group had a higher probability of consuming at least one serving/day of fruits (p = 0.02) and a lower probability of consuming snacks twice/day or more (p < 0.001) than the control group. Conclusions An intervention employing youths as change agents was effective in lowering body weight among community adults in Sri Lanka. Trial registration Trial registration number: SLCTR/2017/002, Name of registry: Sri Lanka Clinical Trials Registry, Date of registration: 19th January 2017, Date of enrolment of the first participant to the trial: 1st February 2017.